ZEB1 transcription factor induces tumor cell PD-L1 expression in melanoma - Chloé Wirbel; Simon Durand; Félix Boivin; Maud Plaschka; Valentin Benboubker; Maxime Grimont; Laetitia Barbollat-Boutrand; Garance Tondeur; Brigitte Balme; Olivier Harou; Anaïs Eberhardt; Stéphane Dalle; et al. (Cancer Immunology, Immunotherapy)
Abstract Tumor cells can evade antitumor immune response by expressing the PD-L1 ligand, leading to the inhibition of PD-1-expressing T lymphocytes. The mechanisms that regulate PD-L1 expression in cancer cells are imperfectly characterized. The transcription factor ZEB1, a major regulator of phenotype switching in melanoma cells, was shown to promote immune escape in melanoma by repressing T cell infiltration. Using inducible models of phenotype switching and ZEB1 gain/loss-of-function melanoma, we show that ZEB1 binds to the CD274 (PD-L1) promoter, directly enhancing PD-L1 mRNA transcription and its expression at the cell membrane. Furthermore, using single-cell spatial analyses on human primary melanoma samples, we demonstrate the correlation of ZEB1 and PD-L1 expression in tumor cells. Overall, these data identify ZEB1-mediated regulation of PD-L1 tumor expression as a mechanism that could contribute to immune escape in melanoma.